Production and Characterization of Bioethanol from Tobacco Stalks via Acid Hydrolysis and Fermentation - Akhmad Irfan; Adi Muslihat; Sunaryo; Sri Jumini; Ikrom Mustofa; Dhandhun Wacano; Raju; Amir Machmud; Endah Kinarya Palupi (International Journal of Hydrological and Environmental for Sustainability, 2026)
The increasing demand for energy and the environmental impacts of fossil fuel consumption have encouraged the development of renewable and sustainable energy sources. Bioethanol derived from lignocellulosic biomass represents a promising alternative fuel due to its renewability and reduced competition with food resources. This study investigates the potential of tobacco stalks, an underutilized agricultural residue, as a feedstock for bioethanol production through acid hydrolysis and fermentation processes. Dried tobacco stalks were hydrolyzed using 1 M sulfuric acid at 110 °C for 3 h to produce fermentable sugars, followed by batch fermentation using Saccharomyces cerevisiae with variations in yeast concentration and fermentation time. The fermentation products were purified by simple distillation and characterized using refractometry, density measurement, GC–MS, and bomb calorimetry. The hydrolysis process yielded a sugar concentration of 7.6%. Refractometric analysis indicated ethanol concentrations in the range of 64–68% (v/v), while density measurements suggested lower effective ethanol purity due to residual water and non-ethanol components. GC–MS analysis confirmed ethanol as the dominant compound, with relative contents ranging from approximately 52% to 73%, accompanied by acetic acid and minor volatile by-products. The calorific value of the produced bioethanol ranged from 4,825 to 4,983 kcal/kg and increased with fermentation time. The results demonstrate that tobacco stalks have considerable potential as a lignocellulosic feedstock for bioethanol production, although further process optimization is required to enhance ethanol purity and overall conversion efficiency.